2020
DOI: 10.1155/2020/8548619
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reactive Oxygen Species and Nitric Oxide in the Inhibition of Trichophyton rubrum Growth by HaCaT Cells

Abstract: Trichophyton rubrum (T. rubrum) is one of the most important agents of dermatophyte infection in humans. The aim of this experiment was to evaluate the effect of HaCaT cells on T. rubrum, investigate the responsible mechanism of action, and explore the role of reactive oxygen species (ROS) and nitric oxide (NO) in the inhibition of T. rubrum growth by HaCaT cells. The viability of fungi treated with HaCaT cells alone and with HaCaT cells combined with pretreatment with the NADPH oxidase inhibitor (DPI) or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…On the other hand, excess ROS reacts with NO to generate highly toxic RNS, further enhancing the therapeutic effects [ 30 , 38 ]. The intracellular NO and RNS levels were investigated after treatments with each agent.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, excess ROS reacts with NO to generate highly toxic RNS, further enhancing the therapeutic effects [ 30 , 38 ]. The intracellular NO and RNS levels were investigated after treatments with each agent.…”
Section: Resultsmentioning
confidence: 99%
“…zeigten, dass die immunologische Funktion von Makrophagen nach einer T. rubrum ‐Infektion verloren ging oder durch Pilz‐Exoantigene und Mannan geschwächt wurde [52]. Vor kurzem wurde beschrieben, dass der Toll‐like ‐Rezeptor (TLR) 2 eine wichtige Rolle bei der Phagozytose von T. rubrum in Monozyten spielt, und dass reaktive Sauerstoffspezies und Stickstoffmonoxid das Wachstum von T. rubrum in Zelllinien in vitro hemmten [49, 53]. Lysin‐M‐Proteine von T. rubrum könnten den Pilz abzuschirmen und es ihm ermöglichen, sich der Immunüberwachung zu entziehen [54].…”
Section: Nichtsyndromale Ichthyosen Und Pilzinfektionenunclassified
“…showed that the immunological function of macrophages was lost following T. rubrum infection or weakened by fungal exoantigens and mannan [52]. Toll‐like receptor (TLR) 2 was recently shown to play an important role in the phagocytosis of T. rubrum in monocytes, and reactive oxygen species and nitric oxide inhibited the growth of T. rubrum in cell lines in vitro [49, 53]. T. rubrum lysin M proteins may help to shield the fungus and allow it to escape immune surveillance [54].…”
mentioning
confidence: 99%